HUBUNGANMOTOR ABILITY DENGAN KECEPATAN MENGGIRING BOLA PADA SISWA PUTRA EKSTRAKULIKULER SD SMP NEGERI SATAP 1 LINGSAR TAHUN 2015 - Wiradarma, I Putu Beny; Hulfian, Lalu; Isnaini, Isnaini (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2018)
This research aimed to know there is or no correlation of speed (speed run 50 meters) and liveliness (zig-zag run) with speed dribble at extracurricular student of SD SMPN Satap 1 Lingsar in year 2015. Sample of this research used population study consist of 20 people. The Â methodÂ of Â thisÂ research used Â experimentalÂ designÂ withÂ multiple correlation design. Instrumental of this research used motor ability test (speed run 50 meters and zig zag run) and speed dribble test. The data analysis used r-test. Based on the result of data analysis showed Â that Â r-test Â wasÂ 0,975. Â The Â conclusion Â of Â this Â research Â showed Â that Â correlation between there variables was very strong.